The Dynamics of Indonesia's National Education Policy: A Public Policy Analysis of National Online Media Coverage - Imam Syafi’i (Journal of Human Interaction and Social Studies, 2026)
This study examines the dynamics of Indonesia's national education policy through a public policy analysis of national online media coverage. A qualitative non-empirical approach employing literature-based document analysis was adopted to investigate how education policies are formulated, implemented, and represented within the digital public sphere. Secondary data were collected from official government publications, national online news media, and relevant scholarly literature. The findings reveal that Indonesia's education policy is characterized by several strategic challenges, including frequent policy adjustments, disparities in educational access, uneven institutional capacity, and the need to improve the quality of human resources through more adaptive educational governance. The analysis also indicates that the government has responded through increased education funding, the implementation of a 13-year compulsory education program, school digitalization, teacher competency development, and improvements in educational infrastructure. National online media play a significant role in communicating policy developments and shaping public understanding of educational reforms. The study concludes that the effectiveness of national education policy depends on policy consistency, institutional coordination, transparent governance, and evidence-based implementation to achieve equitable and sustainable educational development in Indonesia.